IMPROVING CHILD NUTRITION: EVALUATING STUNTING REDUCTION INTERVENTIONS - Dimas, Mohamad Rifki; Tui, Fenti Prihatini Dance; Mozin, Sri Yulianti (Public Policy Journal, 2024)
The purpose of this research is to describe the Regent Regulation No. 77 of 2021 Implementation of the Stunting ReductionProgram Policy in Ayula Tilango Village, Bone Bolango Regency. Based on the following indicators; (a) Policy Standards and Targets, (b) Resources, (c) Inter - Agency Communication, (d) Implementer Characteristics, (e) Economic, Social, and Political Environment, and (f) Implementer Attitudes. This study utilized a qualitative research method with a case study approach. Data was collected through in - depth interviews with various stakeholders, observation, and analysis of policy documents related to stunting program, The research results indicated that the implementation of the stunting program in Ayula Tilango Village faces several challenges, such as budget misalignment and difficulties in creating land for a clean water source. Despite these challenges, the program has achieved some positive impacts, including increased awareness of importance of balanced nutrition, improved acces to healthcare services, and healthier eating habits. However. These impacts still need further enchancement to address stunting issue in Ayula Tilango Village effectively. In conclusion, this research finds that the implementation of the stunting program in Ayula Tilango Village has encountered various obstacles affecting its effectiveness, therefore, greater efforts are needed to improve human resources and allocate budget moe effectively